Analysis, Design and Investigation on a New Single-Phase Switched Quasi Z-Source Inverter for Photovoltaic Application - C. Bharatiraja; P. Sanjeevikumar; Aganti Mahes; Ayushi Saxena; K. Padmapriya; B. K. Mithra; AS Swathimala; S. Raghu (Institute of Advanced Engineering and Science, 2017)
This paper addresses the approach to improve the efficiency of the quasi Z-source inverter. In order to increase the efficiency the reduction of conduction losses is one way to approach. Sequentially to decrease the conduction losses in the quasi z-source inverter the replacement of diode is replacing with switches is proposed which is also called as synchronous rectification. The paper represents basics of the approach, analysis and comparison of the power losses of the traditional and proposed designs of the grid connected PV-system with quasi z-source inverter system. The proposed approach validated on the computer simulations in the MATLAB environment.